39. Comparative One-year Outcomes of Invasive staphylococcus Aureus infections Among Persons with and Without Drug Use in an Urban West Coast Cohort. (31st December 2020) - Appa, Ayesha Ashley; Adamo, Meredith; Le, Stephenie; Davis, Jennifer; Winston, Lisa Gail; Doernberg, Sarah B; Chambers, Henry; Martin, Marlene; Coffin, Phillip; Jain, Vivek
Abstract: Background: Persons who use drugs (PWUD) face substantial risk from invasive Staphylococcus aureus infections but have important demographic and clinical differences from persons without drug use (non-PWUD). Despite this, limited data exist comparing S. aureus infection outcomes in PWUD vs. non-PWUD; these data are needed to inform interventions to optimize care for this vulnerable population. Methods: We identified adults hospitalized from 2013–2018 at two academic hospitals in San Francisco with S. aureus bacteremia or ICD-coded diagnoses of endocarditis, epidural abscess, or vertebral osteomyelitis with compatible S. aureus culture. Via structured chart review, we compared the following among PWUD vs. non-PWUD: clinical and substance use features, adjusted odds of antibiotic completion, and one-year infection-free survival using a multivariate Cox proportional hazards model adjusted for age/race, housing, comorbidities, and MRSA. Results: Of 963 hospitalizations for invasive S. aureus infections in 946 patients, 372/963 (39%) occurred in PWUD. Among PWUD, heroin (198/372, 53%) and methamphetamine use (185/372, 50%) were common (Table 1). Bacteremia occurred in 82% of hospitalizations. PWUD vs. non-PWUD had higher proportions of MRSA (48% vs. 31%) and invasive infections: 20% vs. 12% with endocarditis, 25% vs. 11% with epidural abscess, and 28% vs. 13% with vertebral osteomyelitis (all p< 0.001). PWUD had more self-directed ("AMA") discharges, and most using opioids did not receive methadone or buprenorphine (Table 2). PWUD completed antibiotic courses less often (70% vs. 87%; p< 0.001) and had 2.9-fold higher adjusted odds of incomplete treatment (95% CI:1.7–5.0). One-year mortality was lower in PWUD (18% vs. 30%), but one-year readmission for ongoing/recurrent infection was far higher (28% vs. 14%; HR 1.9 [95% CI:1.3–2.9], Figure 1). Table 1: Demographic, Clinical, and Substance Use Characteristics Table 2: Care Delivery, PWUD vs. non-PWUD Figure 1: One-year Infection-free survival in persons who use drugs (PWUD) vs. non-PWUD Conclusion: PWUD had higher proportions of S. aureus vertebral osteomyelitis, epidural abscess, and endocarditis than non-PWUD, lower odds of treatment completion, and greater risk of infection persistence/recurrence at one year. Among PWUD, opioid and stimulant use were common and undertreated. New patient centered models of care that deliver synchronized S. aureus infection and substance use disorder therapy are urgently needed. Disclosures: All Authors : No reported disclosures